Developing the advanced nurse practitioner role in a memory service. (24th October 2019) - Clibbens, Richard; Depledge, Angela; Hemingway, Steve
Abstract : This article describes how one NHS trust in northern England developed the advanced nurse practitioner (ANP) role within its memory services. It discusses how ANP roles were developed and implemented across four localities of a large NHS trust that provides a number of locally based memory services to improve the diagnostic pathway for people referred to the service and their carers. Advanced practice is considered more broadly followed by a review of the literature related to the role of the ANP and non-medical prescriber in mental health and, more specifically, memory assessment and diagnostic services. Challenges to gaining the requisite competency to work as an ANP are discussed. The need for a clear agreed strategy to ensure practitioner competence and effective governance for the introduction of these roles is described. It is argued that using this model allowed for mental health nurses within memory services to make a major contribution to the transformation of such services and receive recognition for the expansion of their role and appropriate remuneration linked to national NHS employment role profiles. The potential benefit of the ANP role more broadly in mental health services is discussed, together with factors that may have previously hindered their contribution to the transformation of services. The strategic development and planning process that led to implementing the ANP role within memory services is presented, together with a description of how the relevant higher level clinical skills required for the roles were achieved and formally accredited.